KRITIK IDEOLOGIS METODE HISAB DAN RUKYAT (Menyingkap Fungsi Ideologis Term Ummi dalam Penetapan Awal Bulan Islam) - Musonnif, Ahmad (Ahkam: Jurnal Hukum Islam, 2015)
The term ummi refers to the condition in the era of the Prophet Muhammad and sahaba in which they were mostly illiterate. Such illiteracy was used as the reason for the use of hisab to determine the first day of Hijriah month. However, some of the people who use Rukyah have a counterargument since there is a command from the Prophet to see the existence of the moon in determining the first day of the month. Ummi also refers to the Arabic community who has never studied about theory of astronomy. In the context of astronomy method, ummi refers to Muslim who use rukyah (determine the first month on the basis of observation of the moon). This is in contrast to the Jews and Christians who use hisab.Kata kunci: Kritik Ideologis, Metode Hisab-Rukyat, Term Ummi, PenetapanAwal Bulan Islam